2015
DOI: 10.1039/c4ta04841e
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polyether as an all-purpose epoxy modifier: controlled synthesis and toughening mechanisms

Abstract: Controlled synthesis and toughening mechanisms of an all-purpose hyperbranched modifier, which can form non-phase-separated networks with simultaneous enhancements in Tg, modulus, impact and tensile strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 56 publications
11
97
0
Order By: Relevance
“…All curves exhibit as ingle glass transition. [20] The increasei nl ignin content led to an increaseo fFWHM, which is caused by the polydisperse nature of lignin. The storage modulus often depends on the stiffness of the backbone structure and crosslinkd ensity.L ignin is much stiffer than PEGepoxy and possessesm ultifunctional reactive groups;t herefore, the modulus of the network increases with lignin content.…”
Section: Resultsmentioning
confidence: 99%
“…All curves exhibit as ingle glass transition. [20] The increasei nl ignin content led to an increaseo fFWHM, which is caused by the polydisperse nature of lignin. The storage modulus often depends on the stiffness of the backbone structure and crosslinkd ensity.L ignin is much stiffer than PEGepoxy and possessesm ultifunctional reactive groups;t herefore, the modulus of the network increases with lignin content.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of functional monomer can extend the induction time of curing reaction . This extension is beneficial to eliminating the residual stress . Moreover, the introduction of monomer can decrease the curing temperature and accelerate the curing reaction .…”
Section: Resultsmentioning
confidence: 99%
“…D. Foix and co-workers [33] suggested that epoxy group conversion was increased and phase separation was reached during UV curing by the addition of HBP. T. Liu and co-workers [34] reported an epoxideterminated hyperbranched aromatic polyether (EHBPE) that could notably improve the toughness, T g , and tensile strength, and there was a non-phase-separated phenomenon. M. Ganjaee Sari et al [35] carried out surface modification of nanoclay particles by various amounts of polyeater-amide hyperbranched polymer.…”
Section: Introductionmentioning
confidence: 97%